If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -3y + -3y = 4 Combine like terms: -3y + -3y = -6y 26 + -6y = 4 Solving 26 + -6y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + -6y = 4 + -26 Combine like terms: 26 + -26 = 0 0 + -6y = 4 + -26 -6y = 4 + -26 Combine like terms: 4 + -26 = -22 -6y = -22 Divide each side by '-6'. y = 3.666666667 Simplifying y = 3.666666667
| 6x^2+19-8=0 | | 1.5x+25y=600 | | 3x^2+2x+4=12 | | 2x+9=-11-2x | | 3x+45.87= | | 2+3x=-8+x | | lnx+ln(x+7)=1 | | 2z+12=36 | | 10x-y=53 | | 14x+2y=8 | | 2x^3+21x+17x^2=0 | | 5x+3y^2=12 | | 56a+43=32a | | e+r=s | | 3x^2+6x+4=12 | | r=ht | | 81k^2+-1=8 | | 9(9-8x-4x)+8(3x+4)=11 | | r+m=b | | x^3-61=3 | | -4x^2+8x+11=0 | | 12t^2=27+27t | | .5x^2+2x-30=0 | | 10w^2-200=0 | | 8x+-2=6x | | 8x-2=6x | | w^2+11w-200=0 | | lnx=-4.833559 | | (8b^4-b^3)-(b^4+4b^3-4)= | | 4x^4+2x^3-108x-54=0 | | y^2+8x+16=0 | | x^3-9*x-1=0 |